Using Instagram to Teach Writing Descriptive Text - Sulasno Sulasno; Ferisa Indri Hapsari; Erlawati Erlawati (UM Purwokerto Press, 2022)
Writing skill is probably the most difficult skill to master. It is due to the students that may have less experience to write than to read, speak, and even to listen. Descriptive text is one of the five genre texts learned by Junior High School students, especially the 7th and 8th graders. To avoid boredom for the students in learning writing descriptive, the teacher should apply the interesting method in teaching. There are some methods for teaching writing descriptive text using ICT. One of the alternative methods for teaching writing descriptive text is using the application of Instagram. Instagram has become one of the most popular social media today. Moreover, in this pandemic era, when the teaching learning activity is mostly done online, the social media is widely used in virtual class activity. This essay describes the application of Instagram and its features for teaching learning activity. It also explains some procedures of implementing Instagram in learning activity, particularly in writing descriptive text. From this study, the researcher found that the application of Instagram in teaching writing descriptive text is very attractive to the students. It can be seen from the students’ response in the teaching and learning process.